Pendampingan dan Pelatihan Sebagai Upaya Peningkatan Pemasaran Pada Usaha Mikro, Kecil, dan Menengah Roti dan Donat Bakar Yogyakarta - Yasmina Amalia; Yuliawati Yuliawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important sector that supports the community's economy. The COVID-19 pandemic has had a negative impact in the form of a significant decrease in income due to restrictions on product marketing. The new normal situation will make people's lifestyles very dependent on the use of information technology. The aim of this community service is to provide assistance and training in improving marketing. The method in this community service is quantitative descriptive by means of mentoring and training. Marketing digitalization support activities will be carried out in three stages: education, mentoring and sustainability assessment. Training will be provided to increase partners' knowledge and understanding of various digital marketing platforms. The results of this activity are expected to expand partners' knowledge and understanding in the field of marketing digitalization. Mentoring activities are carried out to ensure partners are able to apply the technology and training provided. In the end, the outcome that partners as MSME actors want to achieve is an increase in the economic scale of MSMEs